Anti-White Slavery Legislation and its Legacies in England - Lammasniemi, Laura (Anti-Trafficking Review, 2017)
This paper argues that the foundation of modern anti-trafficking laws in England and Wales was created at the turn of the twentieth century, during the peak of white slavery hysteria. It shows that a series of interrelated legal interventions formed that foundation. While white slavery as a myth has been analysed, this paper turns the focus on legal regulation and shows why it is important to analyse its history in order to understand modern responses to trafficking. It focuses, in particular, on the first legal definition of victims of trafficking, involvement of vigilance associations in law reform, and on restrictions put in place on women’s immigration. Finally, it reflects on how laws enacted at the turn of the twentieth century still resonate with those of today.